Analisis Pemasaran Beras Organik di Provinsi Sumatera Barat (Jurnal Agribisnis Indonesia, 2023)
Rice is one of the leading commodities for organic products, organic rice commodities are one of the widely consumed organic products. West Sumatra Province is one of the regions that have the largest organic rice land in Indonesia. The development of Organic Agriculture has become a policy of the West Sumatra Provincial Government since 2006. There are several problems in marketing organic rice, namely the lack of market access by farmers so that only a small portion of the harvest of organic rice farmers is absorbed as the final product of organic rice and the product is sold at the price of conventional rice. The purpose of this research was to determine and analyze the marketing efficiency and marketing operations (margin, farmer's share, and profit ratio) of organic rice in West Sumatra. The research location is decided by purposive method. To find farmer respondents using purposive sampling and trader respondents using snowball sampling. Qualitative descriptive analysis is used to analyze organic rice marketing channels. Meanwhile, quantitative descriptive is used to measure the marketing efficiency of organic rice using marketing margin analysis, and farmer's share. The results showed that organic rice marketing in West Sumatra consists of 4 marketing channels, which involve five marketing institutions, namely intermediary traders, large traders, city farmers, small-scale retailers, and large-scale retailers (supermarkets). Farmers - intermediary traders - wholesalers - small-scale retailers (channel 2) is the channel pattern chosen by most farmers which are 50%. The most efficient channel pattern is channel 4 because it is the shortest channel with the lowest margin of Rp. 5,500 and the highest farmer's share value of 50%.